Analysis of Supreme Court Decision Number 678 K/Pdt.Sus-PHI/2024 in The Perspective of Labor Law and Industrial Relations - Hutapea, John Gunung; Pangaribuan, Nalom; Saria, Ines Enly; Wijayati, Ani (Innovative: Journal Of Social Science Research, 2025)
of Supreme Court Decision Number 678 K/Pdt.Sus-PHI/2024 examines the application of force majeure in the case of unilateral termination of employment (PHK) between PT Lion Mentari Airline and a foreign worker, Isfarano Neal Brouwer, related to the COVID-19 pandemic. This study analyzes the application of labor law, the protection of workers' rights, and the obligations of employers in crisis situations. The results show that the Supreme Court affirmed the employer's obligation to provide compensation even if the reason for the layoffs is force majeure. This ruling sets an important precedent in labor law, especially regarding the protection of foreign workers and termination of employment in emergency Keywords: Termination of Employment, Force Majeure, Labor Law, Worker Protection, Foreign Workers, Supreme Court